Are Primary Trauma Care (PTC) courses beneficial in low- and middle-income countries - A systematic review. Issue 2 (February 2020) - Kadhum, Murtaza; Sinclair, Pierre; Lavy, Chris
Highlights: Primary Trauma Care course (PTC) was designed to meet the trauma educational needs of front-line staff in LMICs, who lack the resources for ATLS. PTC course improves knowledge, confidence and skills required for the effective team management of trauma, and may reduce overall mortality. Attrition of knowledge and skills is demonstrable after six months, following training on a PTC course. Regular revalidation is recommended. Abstract: Background: Injuries remain an important public health concern, resulting in considerable annual morbidity and mortality. In low- and middle-income countries (LMICs), the lack of appropriate infrastructure, equipment and skilled personnel compound the burden of injury, leading to higher mortality rates. As Advanced Trauma Life Support (ATLS) courses remain uneconomical and inappropriate in LMICs, the Primary Trauma Care (PTC) course was introduced to provide an alternative that is both sustainable and appropriate to local resources. Methods: A systematic review was performed in May 2019, utilising MEDLINE, EMBASE, Cochrane Library and Google Scholar. All studies reporting patient related outcomes (mortality and morbidity rates) and course participant related outcomes (knowledge, confidence and skills) in LMICs were included. PRISMA guidelines were adhered to throughout. Results: Nine observational studies were identified (Level 3 evidence). Six studies reported improved knowledge in injury management post-PTC course ( p < 0.05). Two studies reported improvements in confidence ( p < 0.05) and one on skill attainment ( p < 0.0001). One study reported a reduction in mortality rates post-PTC course ( p < 0.01). Conclusion: Departmental, institutional and personal improvements may occur in clinical practice as a result of formal PTC training of trauma team members in LMICs. Further high-quality research is needed to evaluate this course's effects on observed change in clinical practice and patient outcomes. This may require long-term observational and epidemiological studies to assess improvements in morbidity and mortality. PROSPERO Registration Number: CRD42019133986